Treatment Patterns and Healthcare Costs Among Patients with Stroke and Spasticity: A 2-Year Longitudinal Study - Michael Hull; Vamshi Ruthwik Anupindi; Jing He; Mitchell DeKoven; Jumaah Goldberg; Jonathan Bouchard (Neurology and Therapy)
Abstract Introduction Post-stroke spasticity (PSS) occurs in ~25–43% of patients between 2 weeks and 3 months following a stroke. This retrospective claims study examined the occurrence of spasticity, treatment patterns, healthcare resource utilization, and healthcare costs among patients who experienced a stroke over a 2-year period. Methods Analyses were conducted using healthcare claims from the IQVIA PharMetrics Plus database of commercially/self-insured members from 2015 to 2021. Patients were selected based on two International Classification of Diseases, 10th revision diagnosis codes for stroke requiring an inpatient stay (index date) with continuous enrollment with medical/pharmacy benefits 12 months before (pre-index) and 24 months starting on the index date (post-index). PSS was defined by a diagnosis code for spastic hemiplegia or muscle contracture starting ≥ 7 days post-index, or claims indicating PSS treatment [botulinum toxin A (BoNT-A) or muscle relaxants] any time in the post-index period. A generalized linear model was developed to estimate cost ratios between patients with and without PSS. Results Overall, 7851 patients fulfilled study criteria; 47.7% were treated with physical or occupational therapy, 11.3% with muscle relaxants, and 0.8% with BoNT-A; 12.4% met the post-index definition of PSS; 84.2% were identified using muscle relaxant or BoNT-A codes, 6.6% using diagnosis codes, and 9.2% using both. Median time to codes identifying PSS was 213 days. Patients treated with BoNT-A received an average of three treatments, starting 253 days (median) post-stroke. Mean all-cause healthcare costs were US$62,875 among patients with PSS versus $44,472 among patients without (P < 0.001), representing 39.6% higher adjusted all-cause healthcare costs among patients with PSS versus patients without PSS. Conclusion Patients with PSS utilized numerous treatment modalities and experienced higher mean all-cause healthcare costs than did those without PSS. Earlier identification to optimize treatment of PSS may represent an opportunity for cost savings within managed healthcare systems.